Characteristics of serum chemokine profile in primary biliary cholangitis. (December 2020) - Mu, Ning; Lin, Feng; Jiang, Zhiguo; Liang, Yan; Yang, Zaixing
Highlights: Serum levels of most chemokines are increased throughout development and progression of PBC. Chemokines mainly attractive for neutrophil and eosinophil are decreased in advanced PBC. Chemokines dominantly attractive for Th2 are decreased in early PBC and negatively associated with progression. Abstract: Although chemokines have been believed to exert a pivotal role in pathogenesis of primary biliary cholangitis (PBC), comprehensive analysis of circulating chemokine profile in PBC has been little performed. The aim of this study is to determine serum chemokine profile and to explore its association with the development and progression of PBC. Sixty PBC patients and 30 healthy controls (HC) were enrolled. The sera were detected for 14 chemokines using multiplex immunoassay. The expression of CD3 and CD68 in the portal area of liver tissues was determined by immunohistochemistry in 6 PBC patients. The characteristics of chemokine profile in PBC were analyzed. Serum concentrations of most chemokines were higher, but TARC/CCL17, MDC/CCL22 and ENA-78/CXCL5 were lower in PBC patients than those in HC (all P < 0.05). Most of increased chemokines remained significant in both early and advanced PBC patients. PBC stage was correlated inversely with MCP-4/CCL13(r = −0.373), TARC/CCL17(r = −0.365), ENA-78/CXCL5 (r = -0.418) and I-TAC/CXCL11(r = −0.262), but positively with fractalkine/CX3CL1(r = 0.325). There were significant correlations between serum levels of IP-10/CXCL10 (r = 0.971, P = 0.001) and I-TAC/CXCL11 (r = 0.883, P = 0.020) and CD3 expression within the portal area, and between MIP-3α/CCL20 and CD68 expression within the portal area (r = 0.886, P = 0.019). In PBC patients, there were significant correlations among each other of MCP-4/CCL13, TARC/CCL17, MDC/CCL22, CTACK/CCL27, ENA-78/CXCL5, IP-10/CXCL10, I-TAC/CXCL11, excepting correlations of CTACK/CCL27 with IP-10/CXCL10 and I-TAC/CXCL11. Also, there were strong correlations among each other of CCL3/MIP-1α, CCL4/MIP-1β and IL-8/CXCL8. The only negative correlation was found in the serum between fractalkine/CX3CL1 and TARC/CCL17 (r = −0.311, P = 0.016). Serum levels of most chemokines are increasing throughout the development and progression of PBC, with the exception of chemokines, mainly attractive for neutrophil and eosinophil (e.g. ENA-78/CXCL5, MCP-4/CCL13), decreasing in advanced PBC, and of chemokines, dominantly responsible for Th2 chemotaxis (e.g. TARC/CCL17), decreasing in early PBC and associating negatively with PBC progression.